2009
DOI: 10.1111/j.1365-2036.2009.03989.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of upper gastrointestinal bleeding with oral bisphosphonates and non steroidal anti‐inflammatory drugs: a case‐control study

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…Consistently with our findings, observational studies (OSs) did not found evidence of increased UGIC risk among BP users [15], [16], [19]. However, conversely to our results, BPs – NSAIDs co-therapy has been found to increase the UGIC risk [18], [19]. It should be noticed, that our findings were obtained by contrasting current and past use of BPs, rather than BPs use vs. placebo (or vs. no use) as in RCTs (or in OSs).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently with our findings, observational studies (OSs) did not found evidence of increased UGIC risk among BP users [15], [16], [19]. However, conversely to our results, BPs – NSAIDs co-therapy has been found to increase the UGIC risk [18], [19]. It should be noticed, that our findings were obtained by contrasting current and past use of BPs, rather than BPs use vs. placebo (or vs. no use) as in RCTs (or in OSs).…”
Section: Discussionsupporting
confidence: 92%
“…Pooled analyses found no significant effects for other bisphosphonates [32], [33]. Consistently with our findings, observational studies (OSs) did not found evidence of increased UGIC risk among BP users [15], [16], [19]. However, conversely to our results, BPs – NSAIDs co-therapy has been found to increase the UGIC risk [18], [19].…”
Section: Discussionsupporting
confidence: 89%
“…28 Similarly, our finding that patients with post-index GI events were more frequent users of NSAIDs and glucocorticoids is consistent with previous analyses finding that use of these drugs was predictive of GI events. 29,30 Limitations of our study design include the typical weaknesses of claims database analyses, such as potential coding errors/omissions and the assumption of compliance on the basis of prescription refills. In addition, our combined analysis of different bisphosphonates does not take into account their individual tolerability profiles.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a recent case-control study, no evidence of upper GI bleeding was found in patients administered an oral BP. 11 The mechanism by which BPs injure the gastric mucosa is not fully understood. It has been postulated that BP effects may be similar to nonsteroidal anti-inflammatory drugs in that they cause systemic inhibition of the cyclooxygenase enzyme resulting in decreased synthesis of prostaglandin E 2 (PGE 2 ) in the mucosa.…”
Section: Discussionmentioning
confidence: 99%